"It is not simply the loss of a child": The challenges facing parents who have lost their only child in post-reproductive age in China. Issue 3 (16th March 2021) - Wang, Ning; Hu, Qian
Abstract: The death of one's only child in post-reproductive age (in Chinese, shidu ) is a traumatic event that has specific cultural implications in China. This study investigates the experience of a changed life and emerging challenges amongst Chinese shidu parents. Thematic analysis of 36 interviews revealed four main life consequences following shidu : impairment of psychological and physical health, weakening of social networks and interactions, loss of meaning in life, and lack of care and security. We suggest that health monitoring and mental health intervention, adequate social and community support, and improved social security are the critical needs in this vulnerable group.